Fertilitas dan Daya Tetas Telur Puyuh (Coturnix coturnix japonica) dengan Penambahan Tepung Daun Pepaya (Carica papaya L.) pada Pakan : Fertility and Hatchability of Quail Eggs (Cortunix cortunix japonica) with the Addition of Papaya Leaf Flour (Carica papaya L.) on Feed - Intan Dwi Novieta; Muhammad Arief Alwi; Sultan Mubarak Z; Muhammad Arsan Jamili; Fitriani Fitriani (Universitas Islam Negeri Alauddin Makassar, 2022)
The aim of the study was to determine the effect of papaya leaf powder on fertility and hatchability of quail eggs using a completely randomized design (CRD) method with four treatments and three replications. P0: No control treatment 0%. P1: Papaya leaf flour (Carica papaya L) 1% of the amount of feed. P2: Papaya leaf flour (Carica papaya L) 3% of the total feed. P3: Papaya leaf flour (Carica papaya L) 5% of the total feed. The results showed that the addition of leaf flour at different levels had a significant effect (P<0.05) on the fertility and hatchability of quail eggs. Average egg fertility P0 (86.67%), P1 (100%), P2 (96.67%), P3 (100%), hatchability P0 (65.28%), P1 (86.67%) P2 (79.63%) and P3 (80.00%). The best treatment is P1 treatment with the addition of 1% papaya leaf flour.